7‐year follow‐up after stereotactic ablative radiotherapy for patients with stage I non–small cell lung cancer: Results of a phase 2 clinical trial. Issue 16 (27th March 2017) - Sun, Bing; Brooks, Eric D.; Komaki, Ritsuko U.; Liao, Zhongxing; Jeter, Melenda D.; McAleer, Mary F.; Allen, Pamela K.; Balter, Peter A.; Welsh, James D.; O'Reilly, Michael S; Gomez, Daniel; Hahn, Stephen M.; et al.
Abstract : BACKGROUND: The authors evaluated the efficacy, patterns of failure, and toxicity of stereotactic ablative radiotherapy (SABR) for patients with medically inoperable, clinical stage I non–small cell lung cancer (NSCLC) in a prospective clinical trial with 7 years of follow‐up. Clinical staging was performed according to the seventh edition of the American Joint Committee on Cancer TNM staging system. METHODS: Eligible patients with histologically confirmed NSCLC of clinical stage I as determined using positron emission tomography staging were treated with SABR (50 grays in 4 fractions). The primary endpoint was progression‐free survival. Patients were followed with computed tomography and/or positron emission tomography/computed tomography every 3 months for the first 2 years, every 6 months for the next 3 years, and then annually thereafter. RESULTS: A total of 65 patients were eligible for analysis. The median age of the patients was 71 years, and the median follow‐up was 7.2 years. A total of 18 patients (27.7%) developed disease recurrence at a median of 14.5 months (range, 4.3‐71.5 months) after SABR. Estimated incidences of local, regional, and distant disease recurrence using competing risk analysis were 8.1%, 10.9%, and 11.0%, respectively, at 5 years and 8.1%, 13.6%, and 13.8%, respectively, at 7 years. A second primary lung carcinoma developed in 12 patients (18.5%) at a median of 35 months (range, 5‐67 months) after SABR. Estimated 5‐year and 7‐year progression‐free survival rates were 49.5% and 38.2%, respectively; the corresponding overall survival rates were 55.7% and 47.5%, respectively. Three patients (4.6%) experienced grade 3 treatment‐related adverse events. No patients developed grade 4 or 5 adverse events (toxicity was graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 3.0]). CONCLUSIONS: With long‐term follow‐up, the results of the current prospective study demonstrated outstanding local control and low toxicity after SABR in patients with clinical stage I NSCLC. Regional disease recurrence and distant metastases were the dominant manifestations of failure. Surveillance for second primary lung carcinoma is recommended. Cancer 2017;123:3031–39. © 2017 American Cancer Society . Abstract : To the authors' knowledge, the current prospective study is the first to investigate stereotactic ablative radiotherapy for patients with early‐stage non–small cell lung cancer and presents the longest follow‐up at 7 years. The results demonstrate outstanding overall survival, with locoregional and distant disease control rates for stereotactic ablative radiotherapy that are comparable to those for surgery but with lower toxicity. Close surveillance and aggressive salvage treatment are crucial because many patients with recurrent disease and a second primary malignancy are highly curable.